A Space for Making: Collaborative composition as social participation. Issue 2 (August 2021) - Hart, Adam; Williams, Alan
Abstract : Music composition is traditionally regarded as an act of individual creation and expression, but can be approached, through the aid of digital platforms, as an activity that encourages learning through social participation. This article describes the development of a tablet-based app, Paynter, intended as a digital graphic interface for group collaborative composition and its experimental use in a primary school in Salford, UK, alongside musicians from the BBC Philharmonic orchestra. The app created a framework for a negotiated language of symbols used by two groups of students at Key Stage 1 and Key Stage 2 to tell stories through sound and music. Its functionality enabled compositional thinking to emerge collectively from groups with relatively little exposure to the idea of composing and little knowledge of traditional notational or digital sequencing technologies. The research is grounded in a theoretical context of constructivist approaches to education.